2014
DOI: 10.1111/ibi.12161
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent breeding dispersal and adult survival within a metapopulation ofCommonTernsSterna hirundo

Abstract: Dispersal is increasingly recognized as a process of fundamental importance in population dynamics and other aspects of biology. Concurrently, interest in age‐dependent effects on survival, including actuarial senescence, has increased, especially in studies of long‐lived seabirds. Nevertheless, datasets necessary for studying dispersal and age‐dependent effects are few, as these require simultaneous data collection at two or more sites over many years. We conducted a 22‐year capture‐mark‐recapture study of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…The variance inflation factor (ĉ) was small at 1.12, suggesting a good fit of the most general model with the data (ĉ = 1.0 indicates a perfect fit), and was used in model selection and estimation of the uncertainty around parameter estimates (Spendelow et al 2008;Breton et al 2014). Model selection was therefore based on QAIC c (AIC corrected for overdispersion and small sample size; Burnham and Anderson 2002).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The variance inflation factor (ĉ) was small at 1.12, suggesting a good fit of the most general model with the data (ĉ = 1.0 indicates a perfect fit), and was used in model selection and estimation of the uncertainty around parameter estimates (Spendelow et al 2008;Breton et al 2014). Model selection was therefore based on QAIC c (AIC corrected for overdispersion and small sample size; Burnham and Anderson 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This number is within the range of previous adult survival estimates for Common Terns based on capture-recapture modeling. Most published estimates fall between approximately 0.88 and 0.92 with lower numbers for young adults or very old birds (Nisbet and Cam 2002;Becker 2012, 2015;Zhang et al 2015), and Breton et al (2014) found peak survival of 0.88 in middle-aged adults. However, our estimate for the less productive sites was very low, at 0.70 to 0.72 depending on the model, but with high uncertainty around these estimates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations